Knowledge construction in software companies: systemic approach - Moraes, Cássia Regina Bassan de; Valentim, Marta Lígia Pomim; Souza, Leonardo Pereira Pinheiro de (Faculdade de Filosofia e Ciências, 2019)
Starting from the use of the systemic approach, a discussion was held on the issue of management with people, with a view to building knowledge in organizational environments. For that, in a first moment, elements of the systemic approach are detailed; in the sequence, management issues are approached with people who could lead to the construction of knowledge in organizational environments, with emphasis on information behavior. This research focuses on the scope of Information Technology companies that are dedicated to the development of software, emphasizing their characterization as complex sociotechnical systems. It is also emphasized the complexity involved in software projects and the interrelations between programmers in their teams, clients and stakeholders, organizational structure and aspects of Software Engineering. Both formal and informal information flows are considered as the aggregating element of the different components of the sociotechnical system, which allows the effectiveness of the work. Therefore, a multiple case study was carried out in two software development organizations to verify the consistency of the information flows, regarding the information sharing and its formalization, specifically. The quantitative approach was applied using questionnaires with Likert scale for the employees of the companies, which were analyzed using descriptive statistics. This has resulted in the need to balance information flows, mainly by improving the registration or documentation of information. Finally, the final considerations are made, in order to seek to interrelate the elements addressed in the study.